Hypertension, dietary fiber intake, and cognitive function in older adults [from the National Health and Nutrition Examination Survey Data (2011–2014)] - Zhang, HuanRui; Tian, Wen; Qi, GuoXian; Sun, YuJiao (Frontiers in Nutrition, 2022)
Background Dietary fiber was associated with hypertension (HYP) and cognitive function, but it was unknown whether the effect of HYP on cognitive function in older adults was modified by dietary fiber intake. Methods We recruited 2,478 participants from the 2011–2012 and 2013–2014 National Health and Nutrition Examination Survey (NHANES), with cognitive performance measured by Registry for Alzheimer's disease (CERAD), the Animal Fluency test (AFT), and the Digit Symbol Substitution test (DSST). Multivariate General linear model was used to estimate the interaction between dietary fiber intake and HYP status in association with low cognitive performance. Results Among 2,478 participants, 36% was Controlled HYP, 25% was Low uncontrolled HYP, 11% was High uncontrolled HYP, and 86% was low dietary fiber intake. The association between HYP status and DSST impairment differed by dietary fiber intake for those with high uncontrolled HYP compared to those without HYP. Among participants with low dietary fiber intake, those with uncontrolled HYP had higher risk of DSST impairment compared to those without HYP [HYP ≥ 90/140: OR (95% CI), 1.68 (1.15–2.45); HYP ≥ 100/160: OR (95%CI), 2.05 (1.29–3.23)]; however, there was no association between HYP status and DSST impairment among participants with high dietary fiber intake. Moreover, the interaction of HYP status and dietary fiber intake on DSST was close to statistical significance (P for interaction = 0.057). Conclusions Uncontrolled HYP was associated with poorer cognitive performance in older adults with low, but not high dietary fiber intake. Sufficient dietary fiber intake might be as a new nutrition strategy for the prevention of cognitive impairment in older adults with uncontrolled HYP.